2004
DOI: 10.1038/nature02229
|View full text |Cite
|
Sign up to set email alerts
|

The ADP/ATP translocator is not essential for the mitochondrial permeability transition pore

Abstract: A sudden increase in permeability of the inner mitochondrial membrane, the so-called mitochondrial permeability transition, is a common feature of apoptosis and is mediated by the mitochondrial permeability transition pore (mtPTP). It is thought that the mtPTP is a protein complex formed by the voltage-dependent anion channel, members of the pro-and anti-apoptotic BAX-BCL2 protein family, cyclophilin D, and the adenine nucleotide (ADP/ATP) translocators (ANTs) 1,2 . The latter exchange mitochondrial ATP for cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
721
5
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(765 citation statements)
references
References 20 publications
(19 reference statements)
17
721
5
22
Order By: Relevance
“…Indeed, cardiolipin interacts with and plays a key role for the transport of adenine nucleotides by ANT (Hoffmann, Stöckl, Schlame, Beyer, & Klingenberg, 1994), which has long been considered as a structural component of the mPTP. Although deletion experiments have challenged this hypothesis (Kokoszka et al., 2004), additional data demonstrate a role of ANT in facilitating mPTP opening (Halestrap & Richardson, 2015). The oxidation of cardiolipine, which is tightly bound to ANT, could modify its conformation and facilitate mPTP opening.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, cardiolipin interacts with and plays a key role for the transport of adenine nucleotides by ANT (Hoffmann, Stöckl, Schlame, Beyer, & Klingenberg, 1994), which has long been considered as a structural component of the mPTP. Although deletion experiments have challenged this hypothesis (Kokoszka et al., 2004), additional data demonstrate a role of ANT in facilitating mPTP opening (Halestrap & Richardson, 2015). The oxidation of cardiolipine, which is tightly bound to ANT, could modify its conformation and facilitate mPTP opening.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%
“…Many proteins were thought to form the core of the pore across the mitochondrial membrane but they have been successively ruled out by genetic modulation. This is the case for the voltage‐dependent anion channel (VDAC) and the translocator protein (TSPO) in the outer membrane (Baines, Kaiser, Sheiko, Craigen, & Molkentin, 2007; Kokoszka et al., 2004). Recent data propose a role for ATP synthase as the major component of a multiproteic complex (Bernardi, Rasola, Forte, & Lippe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This finding underlines the major role postulated for CyPD in the formation of the mPTP, and suggests a higher susceptibility to mPTP opening at an older age. Indeed, it was demonstrated that mPTP formation and apoptotic cell death could still occur in the absence of either ANT [57] or VDAC [58]. In contrast, overexpression of CyPD induced mitochondrial swelling and spontaneous cardiac apoptosis, whereas mice lacking cardiac CyPD were protected from ischemia/reperfusion-induced cell death [59].…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 99%
“…Moreover, ANT channel formation is enhanced by Bax (Marzo et al, 1998a), and inhibited by Bcl-2 . However, mouse knockout studies led to the conclusion that ANT would not (always) be required for apoptotic MOMP (Kokoszka et al, 2004). Recent evidence suggests that some ANT isoforms (ANT1, ANT3) are apoptogenic while others are not (ANT2) (Schubert and Grimm, 2004;Zamora et al, 2004).…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%